Reservoir Architecture in Tide-Dominated Estuary: A Case Study of McMurray Formation Oil Sand Reservoir in the Athabasca Block, Canada - Zhang, Weixue; Huang, Jixin; Feng, Wenjie; Wang, Lixin; Shang, Haojie; Yin, Yanshu (Frontiers in Earth Science, 2022)
This paper presents a detailed description of the sedimentary characteristics and architecture model of the tidal-dominated estuary reservoir in the Lower Cretaceous McMurray formation. Based on a thorough study of the core data, 13 lithofacies were recognized. The lithofacies associations were divided into nine types of architecture elements, that is channel, salt marsh, fluvial point bar, tidal point bar, mud flat, mixed flat, sand flat, tidal bar and offshore. Through the combination of high resolution seismic data and well data, the architecture model was established. The boundary surfaces of each architecture elements are depicted and the logging characteristics is concluded. The cross-section is constructed to reveal the superimposition model of different architectural elements with the seismic profiles. The plane and vertical distribution of architectural elements are revealed and the sedimentary model is constructed. In the longitudinal section of estuary, the architecture elements is fluvial deposits (channel, fluvial point bar, and salt marsh), tidal flat (mud flat, mixed flat, and sand flat), tidal bar, tidal flat and offshore from land to sea. In the cross section, tidal bar, sand flat, mixed flat, mud flat, tidal point bar and salt marsh are distributed successively from the center to the sides. Tidal bars and sand flats are the best reservoirs in terms of physical properties. We focus on the analysis of their architecture and summarize their stacking patterns. We propose tidal bars as compounds are lateral accretion. Tidal bar has high-angle continued lateral accretion, with a dip angle of 6–12°. Sand flat also has lateral-migrated characteristics, but their dip angle is 2–6° which is smaller than tidal bars. As a result, the dimension and stack of a single tidal bar and sand flat are quantified. The tidal bar was lateral stacking or vertical stacking with lateral-migrated or forward-migrated sand flat and existed vertical and lateral erosion-filling phenomenon. Tidal bars have width of 100–550 m and length of 800–2,400 m, and sand flats are 300–2,500 m long. Tidal bars and sand flats made up the best reservoirs. The study provides some insights for future research of estuarine sedimentary patterns and reservoir architecture.